Music education in adolescence – A pathway to entrepreneurial identity?. Issue 4 (August 2022) - Jefremovs, Artūrs; Kozlinska, Inna
This study examines the relationship of music education (ME) and entrepreneurship education (EE) received during adolescence with the entrepreneurial identities of university students. Researching adolescent ME alongside EE as a potential enabler of entrepreneurial identity is crucial to understanding the complementarities between ME and EE and so developing knowledge of what kinds of education may contribute to entrepreneurial identity formation. It might also be useful to consider these research insights when developing educational interventions for adolescents. The analysis is based on a sample of 190 Bachelor's-level students from different study backgrounds (business, arts and humanities, etc.) surveyed in one European country. The study finds that both ME and EE received in adolescence are related to entrepreneurial identity in adulthood. However, it is the extra-curricular ME, taken in addition to the secondary school curriculum, that makes the difference and moderates the relationship between EE and identity. The findings contribute to expanding the identity development discourse in the entrepreneurship literature and bring novel insights to EE research by highlighting extra-curricular ME as a potential alternative pathway to entrepreneurial identity development. On a more general level, the study provides an input into the adolescent education literature and learning transfer in education research.